2011
DOI: 10.1371/journal.pcbi.1001138
|View full text |Cite
|
Sign up to set email alerts
|

deFuse: An Algorithm for Gene Fusion Discovery in Tumor RNA-Seq Data

Abstract: Gene fusions created by somatic genomic rearrangements are known to play an important role in the onset and development of some cancers, such as lymphomas and sarcomas. RNA-Seq (whole transcriptome shotgun sequencing) is proving to be a useful tool for the discovery of novel gene fusions in cancer transcriptomes. However, algorithmic methods for the discovery of gene fusions using RNA-Seq data remain underdeveloped. We have developed deFuse, a novel computational method for fusion discovery in tumor RNA-Seq da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
462
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(463 citation statements)
references
References 32 publications
(45 reference statements)
1
462
0
Order By: Relevance
“…Sequencing was performed against the t(10;17)-containing ESS1, and sequence reads were analyzed by using a custom-written deFuse algorithm designed to identify fusion transcripts in RNA sequencing datasets (13), including those involving members of highly homologous gene families. deFuse analysis identified in-frame YWHAE-FAM22A fusions of YWHAE exon 5 to FAM22A exon 2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing was performed against the t(10;17)-containing ESS1, and sequence reads were analyzed by using a custom-written deFuse algorithm designed to identify fusion transcripts in RNA sequencing datasets (13), including those involving members of highly homologous gene families. deFuse analysis identified in-frame YWHAE-FAM22A fusions of YWHAE exon 5 to FAM22A exon 2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of trans-spliced genes has been shown to be critical for understanding the genetic pathways involved in some cancers 56 , such as prostate cancer 57 .…”
Section: Disadvantagesmentioning
confidence: 99%
“…[68][69] To this purpose, a novel computational method, deFuse, has allowed to discover for the first time gene fusions in ovarian cancer specimen, also showing novel chimeric mRNAs in sarcoma. 66 Novel fusion transcripts have been also discovered, especially in breast cancer (Table 1). 51,61 RNA-Seq revealed that the occurrence of chimeric transcripts in melanoma is a frequent event, also highlighting novel genes and pathways previously not associated to its pathogenesis.…”
Section: Rna-seq In Cancermentioning
confidence: 99%